(untitled) (Research, Society and Development, 2021)
Currently, there are several factors that affect women’s health, among them, abortion rates have high rates, especially in emerging countries. In Brazil, the number of legal and illegal abortions has been growing and has been generating serious public health problems. The objective of the research was to know the care of nurses to women in abortion. It`s a descriptive study with a qualitative approach conducted in the hospitalization units of a public municipal maternity hospital in Teresina-PI. The research survey participants were 12 nurses who cared for women. Care nurses and staff were included, and only those who were on vacation or on leave during the research were excluded. For data collection, a semi-structured interview script was used and the data were analyzed using the Content Analysis technique. It was identified that the main care provided by nurses to aborted patients was focused on welcoming, controlling the intensity of the bleeding and emotional support. in a humanized way, especially the psychological aspects. For the care of women to be comprehensive and humanized as proposed by the Humanized Technical Standard on abortion of the SUS, it is necessary that all health professionals and special nurses, be integrated both in the provision of physical care with technical, ethical and legal basis. abortion area, as well as psychological care with qualified listening, affection and welcoming.